REPRESENTASI RUANG TERBUKA HIJAU KAWASAN SUMBER MATA AIR KALI BENOYO DALAM PERSPEKTIF HENRI LEFEBVRE - Bening Hesti Maela; Suryo Sakti Hadiwijoyo; Daru Purnomo (UNIVERSITAS SEBELAS MARET (UNS), 2022)
The lack of use of green open space in an area causes the function of a space to be not optimal, so that the area experiences an imbalance. This study aims to describe the representation of green open space in the Kali Benoyo spring area in the perspective of Henry Lefebvre which includes the dimensions of space practice, representation space and space representation. Henry Lefebvre's theory of space production is divided into three, namely spatial practice, spatial representation and space representation, explaining the area of the Kali Benoyo spring. This study uses qualitative descriptive methods, namely the collection of primary data sources and secondary data. Data collection techniques were carried out using the methods of observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of the study are (1) the form of utilization of green open space as a representation of social space in the Kali Benoyo spring area, namely for bathing, washing clothes, children's play, a place to stop for visitors, and for the photo area (2) social space formed in the area. The water source of Kali Benoyo becomes a living space because the activities of residents in the area cause interaction. (3) The green open space of the Benoyo River spring can be said to be a symbol that is able to transform slum areas into a clean and orderly area.Keywords: Springs, Representation of Space, Social Space, Green Open Space. AbstrakKurangnya pemanfaatan ruang terbuka hijau pada suatu kawasan menyebabkan fungsi suatu ruang menjadi tidak optimal, sehingga kawasan tersebut mengalami ketidakseimbangan. Penelitian ini bertujuan untuk mendeskripsikan representasi ruang terbuka hijau di kawasan sumber mata air Kali Benoyo dalam perspektif Henry Lefebvre yang meliputi dimensi praktik ruang, ruang representasi dan representasi ruang. Teori produksi ruang Henry Lefebvre dibagi menjadi tiga, yaitu praktik spasial, representasi ruang dan ruang representasi, menjelaskan wilayah mata air Kali Benoyo. Penelitian ini menggunakan metode kualitatif deskriptif, yaitu pengumpulan sumber data primer dan data sekunder. Teknik pengumpulan data dilakukan dengan menggunakan metode observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan adalah reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian adalah (1) bentuk pemanfaatan ruang terbuka hijau sebagai representasi ruang sosial di kawasan mata air Kali Benoyo, yaitu untuk mandi, mencuci pakaian, bermain anak, tempat singgah bagi pengunjung, dan untuk area foto (2) ruang sosial yang terbentuk di kawasan sumber mata air Kali Benoyo menjadi ruang hidup karena aktivitas warga di kawasan tersebut yang menimbulkan interaksi. (3) Ruang terbuka hijau sumber mata air Kali Benoyo dapat dikatakan sebagai simbol yang mampu mengubah kawasan kumuh menjadi kawasan yang bersih dan tertata. Kata Kunci: Sumber Mata Air, Produksi Ruang, Ruang Sosial, Ruang Terbuka Hijau.